Nursing diagnoses to the hospitalized patient for correction of aortic aneurysm - Priscilla Veronica Ribeiro; Paula Cristina Nogueira; Vanessa de Brito Poveda (Universidade Federal de Santa Maria, 2017)
Aim: to analyze the most frequent nursing diagnoses given to hospitalized patients for aortic aneurysm surgery and to describe the sociodemographic and clinical profile of those patients. The patients were chosen by the nurses from a specialized in cardiovascular diseases hospital. Method: an exploratory, descriptive, retrospective, quantitative study. The medical records of 65 patients diagnosed with aortic aneurysm were reviewed and the data were analysed in a quantitative way, though descriptive statistics. Results: the majority of the individuals were male (69.2%), sedentary (83.1%) and hypertensive (56.9%). The most prevalent nursing diagnoses were: risk of infection, risk of constipation, risk of sleep deprivation, risk for decreased cardiac output, family bond rupture and fall risk. Final considerations: in order to list reliable nursing diagnoses, nurses must use his/her competence, ability, clinical and theoretical attitude, to establish consistent priorities with the patient's present state of health and, thus, institute assertive and resolutive interventions, evaluating in a continuous way the nursing process